Consistent Targeted Dosing of BUD Benefits Asthma Patients Needing Long-Term Oral Corticosteroids - Nierengarten, Mary Beth (MD Conference Express, 2014)
In patients with severe asthma who depend on long-term oral corticosteroid therapy, additional treatment with consistent doses of budesonide (BUD) delivered by a novel inhalation system significantly improved lung function and control of asthma exacerbations. This article discusses outcomes from the AKITA Inhaled Steroid Suspension for Inhalation in Subjects With Asthma [AICS; NCT01200108; Canisius S et al. Am J Respir Crit Care 2014]